The Dynamics of Wayang Golek in Pandemic and Globalization: Traditional Art Sustainability - Islamy, Mohammad Rindu Fajar; Abdussalam, Aam; Adzkia, Giani (el Harakah: Jurnal Budaya Islam, 2021)
This research aims to explore the dynamics of wayang golek art and to highlight its sustainability in the future. Modernity, the acceleration of technological devices and globalization wave in the last two decades, transfers great pressure on traditional arts and culture. Wayang Golek, a performing art originally from West Java, has recently received a fairly strong wave of resistance due to changes in the social culture which is mainly leading to modernity. By using a qualitative approach, data collection techniques were carried out by interviewing two main players as the puppeteers of Wayang Golek. The data analysis uses the theory of Miles and Hubberman, and the theoretical review of Islamic studies. The results of the study show that 1) Wayang Golek has unique characteristics, where the talent needed tends to go through the "inheritance" tradition, 2) Wayang Golek can be a bridge for internalizing religious and humanist values for the community through unique stories based on custom, 3) the restriction of Wayang Golek performance due to the Covid-19 pandemic leads the puppeteers to be more creative to survive, such as creating videos and uploading them in YouTube and other social media, and 4) the preservation of this art depends on the serious attention of all parties, from the government, regional officials, and the community. Penelitian ini bertujuan untuk mengeskplorasi dinamika kesenian wayang golek, serta menyoroti keberlangsungan ‘hidup’ seni tradisional wayang golek dimasa yang akan datang. Era modernitas, akselerasi perangkat teknologi dan gelombang arus globalisasi dalam dua dekade terakhir, memberikan tekanan hebat pada wilayah seni dan budaya tradisional. Wayang Golek sebuah seni pertunjukkan yang berasal dari Jawa Barat akhir-akhir ini mengalami gelombang resistensi cukup kuat imbas dari perubahan kultur sosial masyarakat yang bergerak kearah modernitas. Dengan menggunakan pendekatan kualitatif, teknik pengumpulan data dilakukan dengan wawancara terhadap dua pemain utama sebagai “Dalang” Wayang Golek, observasi dan dokumentasi. Adapun analisis data menggunakan teori Miles dan Hubberman, dan kajian teoritis Islamic studies. Hasil penelitian menunjukkan bahwa 1) Seni Wayang Golek memiliki karakteristik unik, dimana bakat yang dibutuhkan cenderung melalui tradisi “warisan”, 2) Wayang Golek dapat menjadi jembatan internalisasi nilai-nilai religius dan humanis bagi masyarakat melalui cerita-cerita unik berbasis adat, 3) dilarangnya pagelaran Wayang Golek akibat pandemi Covid-19 membuat para dalang lebih kreatif untuk bertahan, seperti membuat video dan menunggahnya ke YouTube dan media sosial yang lain, dan 4) Kelestarian kesenian ini bergantung terhadap perhatian serius semua pihak baik dari pemerintah, pejabat daerah, maupun masyarakat.